2022
DOI: 10.5761/atcs.oa.21-00236
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic-Dose Warfarin (International Normalized Ratio >1.6) Plus Aspirin Improved Long-Term Patency of Saphenous Vein Graft without Bleeding Complication

Abstract: Purpose: Saphenous vein graft (SVG) is the most commonly used conduits in coronary artery bypass grafting (CABG), but the disadvantage of SVG is its tendency for progressive failure. We hypothesized that therapeutic-dose warfarin (international normalized ratio [INR] >1.6) plus aspirin improve SVG patency. This study aimed to evaluate the factors contributing to SVG patency. Methods: Since 2010–2020, 199 patients who underwent isolated CABG using SVG were divided into two groups according to their I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Warfarin was postoperatively administered to more than two-thirds of eligible patients (67.3%), because our previous study showed that its therapeutic dose in combination with aspirin improves long-term venous graft patency. 15 All patients underwent early postoperative (13.3±6.3 days) and 1-year (12.8±2.8 months) angiographic evaluations. The GEA anastomotic diameter was 2.70±0.58 mm at the early postoperative evaluation.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Warfarin was postoperatively administered to more than two-thirds of eligible patients (67.3%), because our previous study showed that its therapeutic dose in combination with aspirin improves long-term venous graft patency. 15 All patients underwent early postoperative (13.3±6.3 days) and 1-year (12.8±2.8 months) angiographic evaluations. The GEA anastomotic diameter was 2.70±0.58 mm at the early postoperative evaluation.…”
Section: Surgical Proceduresmentioning
confidence: 99%